COVERAGE OF COSTS RELATED TO TRAINING UNDER THE TRAINING CONTRACT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Through this article, the compensation of the costs specified in the industrial training contract adopted in the new version of the Labor Code, the responsibility for the costs between the student and the employer arising as a result of labor relations, and in what cases this responsibility is applied, as well as the world the analysis of the opinions expressed by labor law scholars regarding reimbursement of costs is highlighted.